Investigating the spectrum of dermatologic manifestations in COVID‐19 infection in severely ill patients: A series of four cases. (28th September 2020) - Occidental, Michael; Flaifel, Abdallah; Lin, Lawrence H.; Guzzetta, Melissa; Thomas, Kristen; Jour, George
Abstract: COVID‐19, an infectious disease caused by the novel coronavirus, was initially identified in Wuhan, China, in December 2019. By March 2020, it was declared a pandemic by the World Health Organization. Although most findings have been reported in the lungs, primarily due to catastrophic respiratory decline, other organs, including the skin, are affected. Recent reports have been published describing the clinical spectrum of COVID‐19‐related lesions. In addition, recent case series have described a subset of these lesions having underlying thrombotic microangiopathy with increased complement activation characterized by increased C4d deposition within the blood vessel walls. Herein, we describe a series of COVID‐19‐related cutaneous manifestations found at autopsy examination and their underlying histopathologic findings. Although the clinical manifestations seen in these lesions vary widely, the underlying etiology of thrombotic microangiopathy remains consistent and reproducible.